Immunoprotective responses of T helper type 1 stimulatory protein‐S‐adenosyl‐L‐homocysteine hydrolase against experimental visceral leishmaniasis. (27th April 2016) - Khare, P.; Jaiswal, A. K.; Tripathi, C. D. P.; Sundar, S.; Dube, A.
Summary: It is well known that a patient in clinical remission of visceral leishmaniasis (VL) remains immune to reinfection, which provides a rationale for the feasibility of a vaccine against this deadly disease. In earlier studies, observation of significant cellular responses in treated Leishmania patients as well as in hamsters against leishmanial antigens from different fractions led to its further proteomic characterization, wherein S‐adenosyl‐L‐homocysteine hydrolase (AdoHcy) was identified as a helper type 1 (Th1) stimulatory protein. The present study includes immunological characterization of this protein, its cellular responses [lymphoproliferation, nitric oxide (NO) production and cytokine responses] in treated Leishmania ‐infected hamsters and patients as well as prophylactic efficacy against Leishmania challenge in hamsters and the immune responses generated thereof. Significantly higher cellular responses were noticed against recombinant L. donovani S‐adenosyl‐L‐homocysteine hydrolase (rLdAdoHcy) compared to soluble L. donovani antigen in treated samples. Moreover, stimulation of peripheral blood mononuclear cells with rLdAdoHcy up‐regulated the levels of interferon (IFN)‐γ, interleukin (IL)−12 and down‐regulated IL‐10. Furthermore, vaccination with rLdAdoHcy generated perceptible delayed‐type hypersensitivity response and exerted considerably good prophylactic efficacy (∼70% inhibition) against L. donovani challenge. The efficacy was confirmed by the increased expression levels of inducible NO synthase and Th1‐type cytokines, IFN‐γ and IL‐12 and down‐regulation of IL‐4, IL‐10 and transforming growth factor (TGF)‐β. The results indicate the potentiality of rLdAdoHcy protein as a suitable vaccine candidate against VL.